PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA TERHADAP KINERJA PEJABAT STRUKTURAL DI LINGKUNGAN UNIVERSITAS MULAWARMAN - Syaharuddin Y (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2015)
The purpose of this study was to Know and analyze any significant relationship between the ability of employees, education and training as well as experience working together on structural officials in environment the university Mulawarman and also to analyze the influence of dominant among employability, education and training, and experience work on structural officials in environment the university Mulawarman. In this study used three variables studied, among others, the ability of employees (X1), education and latiha (X2) and work experience (X3). From the results of the regression analysis above, it can be arranged the following equation: Y = 0.521 + 0.252 + 0.577 X1 X2 X3 + 0.219 + e Variable capability of employee, Education and Training, Work Experience, simultaneously affect the performance of structural officials Mulawarman employees. Simultaneous influence on employee performance structural officials Mulawarman by 68.00%, while the remaining 32.00%, influenced the other, is evident from the results of the test F by F count> F table value and significance value of 0.000 <? = 0 , 05, then the ability of work, education and training, work experience, affect the performance of structural officials attested employees university Mulawarman.